High foliar nutrient concentrations and resorption efficiency in Embothrium coccineum (Proteaceae) in southern Chile1. Issue 2 (1st February 2015) - Fajardo, Alex; Piper, Frida I.
Abstract : Premise of the study: Southern South American (SA) Proteaceae species growing in volcanic soils have been proposed as potential ecosystem engineers by tapping phosphorus (P) from soil through their cluster roots and shedding nutrient‐rich litter to the soil, making it available for other species. We tested whether Embothrium coccineum (Proteaceae) has effectively lower P nutrient resorption efficiency and higher litter P concentrations than co‐occurring, non‐Proteaceae species. Methods: In southern Chile, we assessed the P and nitrogen (N) resorption efficiency of senescent leaves and fresh litter of E. coccineum and co‐occurring tree species in a soil fertility and moisture gradient (600–3000 mm of annual precipitation) in Patagonia, Chile. We determined P and N concentrations, leaf mass per area (LMA), and ratios of N/P and C/N in mature and senescent leaf cohorts and fresh litter. Key results: Embothrium coccineum showed significantly higher P and N resorption efficiency than co‐occurring species; in fact, E. coccineum fresh litter had the lowest P‐content. While E. coccineum showed significantly lower fresh litter P concentrations than the rest of the species, it showed significantly higher N concentrations. Embothrium coccineum also had lower LMA and similar N/P and C/N ratios when compared with co‐occurring tree species. Conclusions: We found that E. coccineum efficiently mobilized P and, to a lesser extent, N before leaf shedding. We did not find support for the ecosystem engineering hypothesis via shedding P‐rich litter. We suggest that southern South American Proteaceae may be taking up other nutrients besides P, probably N, from the young, volcanic soils of this region.